Towards Inclusive Governance: Regulatory Innovations in Licensing to Protect Indigenous Rights (Contrarius Series: Law & Social Justice, 2026)
Changes to Indonesia's licensing system through Law Number 11 of 2020 and Government Regulation Number 28 of 2025 have improved government efficiency and digitalization. However, these changes have not adequately addressed inclusion and the rights of indigenous peoples. This study aims to explore innovations in licensing regulations to protect indigenous rights through three main approaches: procedural, substantive, and institutional innovation.  Procedural innovation involves indigenous communities in public consultations, in line with the principle of Free, Prior, and Informed Consent (FPIC). Substance innovation calls for integrating customary law and local wisdom into regulations, aligning state law with local practices. Institutional innovation seeks to strengthen cooperation between the government and indigenous institutions to address licensing issues. The findings suggest that inclusive licensing promotes social legitimacy, ecological justice, and culturally based sustainable development. Thus, recognizing customary law is crucial for developing fair governance that reflects local wisdom.